Analisis Tantangan Baru Nilai Publik dan Akuntabilitas di Era Digital - R. Neneng Rina Andriani; Dermawan, Wildan Dwi; Adil Ridlo Fadillah (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2025)
This study aims to investigate the development of publications on public value and accountability and find future prospects for the topic. Data were observed from Dimension AI database with the keywords "public value" AND "accountability". There are 377 documents consisting of articles, book chapters, conference papers, editorials, letters, notes, and reviews with a publication time span from 1976 to 2023. The research method is bibliometric analysis, using R biblioshiny and VosViewer software. The results found that the development of publications every year tends to increase, followed by an increase in author citations. The most productive journal and has the greatest impact is Public Money & Management and the most productive author and has the greatest impact is Giuseppe Grossi. Public Sector and Corporate Governance are topics that often appear. While the topic that is often discussed lately is transparency. Overall, these topics are predicted to be topics that will be discussed in the future.